Caracterización de la baja tolerancia a la frustración en un paciente, aproximación desde la trec - Avilés Sánchez, Abdel Yashin (2020)
When a person faces an unforeseen situation or inconvenient, the low tolerance to frustration causes that the individual generates a series of thoughts that end up leading to an exaggeration of the feeling of discomfort that in turn provokes a series of reactions that can end in hostility, although people's reactions may be different, therefore, this study is based on the identification of the characteristics of low tolerance to frustration from the point of view of rational emotional-behavioral therapy studying and applying thus the basic structures of the same, for which information collection techniques such as the interview, the clinical history, the observation and psychometric tests were implemented that helped the diagnosis and develop a therapeutic scheme.